STRATEGI MANAJEMEN KELAS DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI MTSN DARUL IHSAN ABU HASAN KRUENG KALEE, ACEH BESAR - Swirda Wati; Sufriadi Sufriadi; Hazal Fitri; Safriadi Safriadi (Jurnal Manajemen Pendidikan, 2026)
Learning motivation is a key factor influencing students’ success in achieving learning objectives. This study aims to describe classroom management strategies at MTsN Darul Ihsan Abu Hasan Krueng Kalee and their contribution to students’ learning motivation. This study is based on Self-Determination Theory (SDT), which focuses on the fulfillment of psychological needs such as autonomy, competence, and relatedness. This study employs a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation, and were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results indicate that teachers implement comprehensive strategies, including creating a comfortable classroom environment, establishing shared classroom rules, enforcing discipline, and conducting systematic lesson planning through modules and lesson plans. Additionally, the use of varied methods such as quizzes, games, and rewards has proven effective in enhancing learning motivation. These strategies were able to increase learning motivation, reduce boredom, and encourage active student participation. The implications of this research indicate that well-planned, humanistic, and student-centered classroom management can meet the needs for autonomy, competence, and relatedness, thereby fostering sustainable learning motivation.